1987
DOI: 10.1021/bi00388a023
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle stage-dependent variations in drug-induced topoisomerase II mediated DNA cleavage and cytotoxicity

Abstract: The DNA cleavage produced by 4'-(9-acridinylamino)methanesulfon-m-anisidide (m-AMSA) in mammalian cells is putatively mediated by topoisomerase II. We found that in synchronized HeLa cells the frequency of such cleavage was 4-15-fold greater in mitosis than in S while the DNA of G1 and G2 cells exhibited an intermediate susceptibility to cleavage. The hypersensitivity of mitotic DNA to m-AMSA-induced cleavage was acquired relatively abruptly in late G2 and was lost similarly abruptly in early G1. The susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(24 citation statements)
references
References 30 publications
5
19
0
Order By: Relevance
“…The same conclusion of a role for topoisomerase II in decatenation was proposed in the case of rDNA minichromosomes, for which we found enhanced topoisomerase II cleavage although transcription was off (26). It is noteworthy that early experiments using alkaline elution suggested that overall DNA cleavage induced by topoisomerase II poisons in mammalian cells was considerably increased during mitosis (38,39). In the same way, since the gene is replicated during the first 10 min of S phase, it is tempting to speculate that occurrence of topoisomerase II sites at this time correlates with rapid chromosome decondensation after metaphase, to allow replication fork passage throughout this region.…”
Section: Discussionsupporting
confidence: 85%
“…The same conclusion of a role for topoisomerase II in decatenation was proposed in the case of rDNA minichromosomes, for which we found enhanced topoisomerase II cleavage although transcription was off (26). It is noteworthy that early experiments using alkaline elution suggested that overall DNA cleavage induced by topoisomerase II poisons in mammalian cells was considerably increased during mitosis (38,39). In the same way, since the gene is replicated during the first 10 min of S phase, it is tempting to speculate that occurrence of topoisomerase II sites at this time correlates with rapid chromosome decondensation after metaphase, to allow replication fork passage throughout this region.…”
Section: Discussionsupporting
confidence: 85%
“…Iftopoisomerase II were phosphorylated during mitosis, one would expect an ==10-fold increase in activity (taking into account the increase in enzyme content prior to mitosis). In fact, 4-to 15-fold more topoisomerase II activity was detected in mitotic HeLa cells than in an S-phase population (38). Phosphorylation may be responsible for rapid changes in activity in response to intracellular signals, whereas alterations in the amount of protein may be required for the gross structural reorganization of the genome during mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…A number of investigators have demonstrated a dissociation between drug-induced DNA cleavage and cytotoxicity in the various stages of the cell cycle. Estey et al (1987) reported that in HeLa cells maximum DNA cleavage was produced in mitosis, whereas maximum cytotoxicity occurred in S-phase cells. Similar observations have been reported in 3T3 cells (Chow & Ross, 1987;Markovits et al, 1987).…”
Section: Cellular Recognition Of Dna Damagementioning
confidence: 99%